METHODS AND FORMS OF ORGANIZING THE EDUCATIONAL PROCESS IN PRESCHOOLS - Akhmedova, Khurshida (Confrencea, 2024)
In the pre-school education organization, it is an important task to set up management work correctly in the process of moral and moral education of pre-school children. In this article, we will get acquainted with the normative basis of establishing management in preschool educational organizations